Antitumor platinum(II) complex 56MESS binds to DNA G-quadruplexes, downregulates expression of c-MYC and k-RAS oncogenes, and triggers DNA damage in cancer cells - Malina, Jaroslav; Kostrhunova, Hana; Aldrich-Wright, Janice R; Brabec, Viktor (Chemico-biological interactions, 2025)
Previous research indicated that the cytotoxic activity of the antitumor platinum(II) complex [Pt(1S,2S-diaminocyclohexane)(5,6-dimethyl-1,10-phenanthroline)]2+ (56MESS) was not primarily attributed to DNA binding, despite the complex being confirmed to localize also in the nucleus. In this study, we have demonstrated that the antiproliferative activity of 56MESS indeed involves DNA binding. Furthermore, in addition to binding duplex DNA, the complex also interacts with non-canonical secondary DNA structures, such as G-quadruplexes (G4s) and i-Motifs (iMs). This interaction leads to the suppression of G-regulated oncogene expression and disrupts key enzymatic processes associated with DNA, potentially contributing to DNA damage and the biological activity of 56MESS. These findings build upon previously published results, revealing that the anticancer activity of 56MESS is significantly more multifaceted than previously understood, involving multiple distinct mechanisms.
Keywords: down regulace; protoonkogenní proteiny c-myc; protoonkogenní proteiny p21(ras); poškození DNA; DNA i-Motif; protinádorové látky; DNA Damage; Cell Line, Tumor; Cell Proliferation; Organoplatinum Compounds; k-RAS oncogene; G-Quadruplexes; Down-Regulation; lidé; Humans; Proto-Oncogene Proteins c-myc; DNA; proliferace buněk; Proto-Oncogene Proteins p21(ras); G-kvadruplexy; nádorové buněčné linie; Antitumor platinum complex; DNA G-quadruplex; organoplatinové sloučeniny; c-MYC oncogene; Antineoplastic Agents